Optimum usage of prilocaine-lidocaine cream in premature ejaculation - Atikeler, MK; Gecit, I; Senol, FA (Blackwell Verlag Gmbh, 2002)
Premature ejaculation is a common male sexual disorder in which orgasm and ejaculation occur before the desired moment. The primary therapeutic approach to premature ejaculation has been behavioural and pharmacotherapy. In this study, we evaluated the efficacy and optimum usage of lidocaine-prilocaine cream 5% in preventing premature ejaculation. Forty patients were examined in the study group and randomized into four groups, each comprising 10 patients. Patients in group 1 applied lidocaine-prilocaine cream 5% for 20 min, the patients in group 2 applied it for 30 min, and the patients in group 3 applied the cream for 45 min before sexual contact, with all patients covering the penis with a condom. Patients in the fourth group applied a base cream as placebo. In group 1, the pre-ejaculation period increased to 6.71 +/- 2.54 min without any adverse effects. In group 2, although the pre-ejaculation period increased in four patients up to 8.70 +/- 1.70 min, six patients in this group and all patients in group 3 had erection loss because of numbness. In the placebo group, there was no change in their pre-ejaculation period. Therefore, lidocaine-prilocaine cream 5% is effective in premature ejaculation and 20 min of application time before sexual contact is the optimum period.
Keywords: premature ejaculation; prilocaine; lidocaine cream